Representation increases women's influence in climate deliberations: Evidence from community-managed forests in Malawi - Clayton, Amanda; Dulani, Boniface; Kosec, Katrina; Robinson, Amanda Lea (Wiley, 2026)
Women's inclusion is now the norm in global and local initiatives to combat climate change. We examine how women's representation affects climate deliberations using the case of community-managed forests in Malawi. We run a lab-in-the-field experiment randomly varying the gender composition of six-member groups asked to deliberate on policies to combat local overharvesting. We find that any given woman has relatively more influence in group deliberations when women make up a larger share of the group, a change driven by men's assessments of women's influence. Women's presence also shifts the content of deliberations toward prospective solutions for which women have socially recognized expertise (cooking and replanting). Despite these changes, women and men do not prefer different deforestation policies, and women's presence does not meaningfully affect group decisions. Our work demonstrates how women's presence shapes climate deliberations but also calls into question claims that women's inclusion will necessarily affect climate decisions.